Архітектоніка екосистемного підходу в прийнятті публічно-управлінських рішень - Kalashnik, N. S. (Forestry Education and Science: Current Challenges and Development Prospects, 2024)
The study examines the ecosystem approach to public governance, which ensures sustainable decision-making by integrating environmental, social and economic factors. It is emphasized that the steps of making management decisions according to the ecosystem approach include: problem identification, stakeholder engagement, data analysis, scenario development, policy development, implementation and adaptive management, promoting resilience and inclusiveness. It specifically emphasizes the role of civil society and the shift in focus from directive to adaptive management when applying the ecosystem approach.